1996
DOI: 10.1074/jbc.271.37.22422
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Low Density Lipoprotein (LDL) Receptor Pathway in the Metabolism of Chylomicron Remnants

Abstract: Two receptor pathways are thought to mediate the hepatic clearance of chylomicron remnants, (i) the low density lipoprotein receptor (LDLR) pathway and (ii) non-LDLR pathway. The current study was undertaken to quantitatively assess the contribution of each receptor pathway to hepatic catabolism of chylomicron remnants, by using mice that are deficient in apolipoprotein E (apoE) (apoE(؊/؊)), the LDLR (LDLR(؊/؊)), and both (apoE(؊/؊);LDLR(؊/؊)). Vitamin A fat tolerance tests showed that the area under the curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 46 publications
5
42
0
Order By: Relevance
“…These observations are consistent with our previous findings that the LDLR plays a pivotal role in the metabolism of chylomicron (27). In the present study, however, no significant difference was observed in the plasma excursion of retinyl ester between the LDLRKO mice with and without the apo E transgene (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…These observations are consistent with our previous findings that the LDLR plays a pivotal role in the metabolism of chylomicron (27). In the present study, however, no significant difference was observed in the plasma excursion of retinyl ester between the LDLRKO mice with and without the apo E transgene (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…It should be noted that ApoE lipoproteins are unusual; they are cholesterol enriched and lack ApoE. However, their rapid turnover in these mice, as opposed to the slow turnover of CM-RE in ApoE knock-out mice (55), suggests that the particles have acquired ApoE from their recipients. Thus, our data strongly imply that much of the lipoprotein core lipid uptake into the heart occurs via lipid shedding.…”
Section: Discussionmentioning
confidence: 94%
“…The LDL receptor (LDL-R) accounts for most of LDL removal and contributes to part of the uptake of chylomicron remnants (4,5). This highly informative endocytic receptor prototype nevertheless leaves two unsolved issues regarding apoB-containing lipoprotein clearance.…”
Section: Triglyceride (Tg)mentioning
confidence: 99%